Acceptability of an Adolescent Self‐Management Program for Juvenile Idiopathic Arthritis. Issue 2 (17th November 2021) - Chomistek, Kelsey; Barnabe, Cheryl; Naqvi, Syeda Farwa; Birnie, Kathryn A.; Johnson, Nicole; Luca, Nadia; Miettunen, Paivi; Santana, Maria J.; Stinson, Jennifer; Schmeling, Heinrike
Abstract : Objective: The study objective was to test the acceptability of a self‐management program (SMP) for adolescents with juvenile idiopathic arthritis (JIA) focused on disease information, self‐management, and social support needs. Methods: This study was conducted using inductive qualitative methods to explore the acceptability of an in‐person/videoconference SMP. Two groups of four adolescents with JIA (mean age = 13.5, SD  =  0.8) and two groups of pediatric rheumatology health care professionals (n = 4, n = 5) participated in four feedback sessions each. The SMP was presented to study participants, and feedback was provided on the content, format, and structure of the program. Thematic analysis was used to analyze the data. Results: Adolescents felt that the content was appropriate and would be effective in supporting self‐management of their arthritis. Participants advised that the trustworthiness of the information would be increased if a rheumatology health care provider facilitated the session. Potential barriers to participation included distance and availability (weekdays and times), but the option for videoconference‐based participation was an appropriate solution to both of these issues. Minor changes were made to content and format, and required changes were made to address participant recommendations for improvement. Conclusion: This study confirmed the acceptability of an in‐person/videoconference SMP for patients with JIA. Modifications were made to the SMP based on the focus group feedback, and future directions include a pilot randomized controlled trial to assess feasibility and preliminary effectiveness of the program.